KONFLIK PENGUASAAN DAN PENGUSAHAAN SUMUR TUA MINYAK DAN GAS BUMI DI KABUPATEN BOJONEGORO, JAWA TIMUR - Subadi Subadi (Arena Hukum, 2023)
The conflict of control and exploitation of old oil and gas wells in Bojonegoro Regency is a latent conflict between the people or groups of miners and Pertamina EP Asset IV Field Cepu, which is latent and difficult to resolve. This normative legal research, supported by in-depth interviews, aims to find the legal aspects of control and exploitation by the people and the multiple conflicts that occur as well as ideas for their resolution. The results show: 1) Pertamina EP's control and exploitation of old wells is based on statutory regulations, while the control and exploitation by the people is only based on customary law. 2) Differences in perception between Pertamina EP can be settled through: a) legalizing, facilitating requirements and shortening the bureaucracy for licensing upstream and downstream activities by the people; b) reducing the ambiguity attitude of Pertamina EP which does not want to work on old wells but still hopes for the results; c) Pertamina EP, the Regional Government and Perhutani should continue to provide guidance, supervision.